PENGARUH ROL DINGIN DAN ANIL TERHADAP KARAKTERISTIK STRUKTUR MIKRO DAN KEKERASAN MIKRO PADUAN Zr-0,5%Nb-Si - Hardiyanti, Heri; Adhi, Arief Sasongko; Setiawan, Jan (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
EFFECTS OF COLD-ROLLING AND ANNEALING ON THE MICROSTRUCTURE AND MICROHARDNESS CHARACTERISTICS OF Zr-0.5%Nb-Si. The performance improvement of zirconium alloys can be done by adding a certain percentage of common alloying elements such as Nb and Si. The addition of Nb provides resistance to irradiation and stabilizes the β phase (which normally forms at high temperatures) at room temperature. The addition of Si increases the strength of the alloys. The synthesis of a Zr-0.5% Nb-Si alloy have been carried out using an electric arc furnace. The microstructure and the microhardness of this alloy were observed after cold-rolling and annealing. It can be seen from the annealed alloy without cold-rolling that the grain size is larger with reduced microhardnes. The alloy treated with cold-rolling shows changes in the microstructure while the deformation density increases, which results in an increase in microhardness. Heat treatment to the cold-rolled alloy changes the microstructure of the alloy where recrystallization occurs, and the deformation density decreases, which results in the decreasing of microhardness. The lowest grain size and microhardness for the alloy that was cold-rolled at ε = 0.8 and annealed are 0.302 mm and 187 HVN, respectively.